Regulatory Coordination between Two Major Intracellular Homeostatic Systems: HEAT SHOCK RESPONSE AND AUTOPHAGY - Dokladny, Karol (American Society for Biochemistry and Molecular Biology, 2013)
The eukaryotic cell depends on multitiered homeostatic systems ensuring maintenance of proteostasis, organellar integrity, function and turnover, and overall cellular viability. At the two opposite ends of the homeostatic system spectrum are heat shock response and autophagy. Here, we tested whether there are interactions between these homeostatic systems, one universally operational in all prokaryotic and eukaryotic cells, and the other one (autophagy) is limited to eukaryotes. We found that heat shock response regulates autophagy. The interaction between the two systems was demonstrated by testing the role of HSF-1, the central regulator of heat shock gene expression. Knockdown of HSF-1 increased the LC3 lipidation associated with formation of autophagosomal organelles, whereas depletion of HSF-1 potentiated both starvation- and rapamycin-induced autophagy. HSP70 expression but not expression of its ATPase mutant inhibited starvation or rapamycin-induced autophagy. We also show that exercise induces autophagy in humans. As predicted by our in vitro studies, glutamine supplementation as a conditioning stimulus prior to exercise significantly increased HSP70 protein expression and prevented the expected exercise induction of autophagy. Our data demonstrate for the first time that heat shock response, from the top of its regulatory cascade (HSF-1) down to the execution stages delivered by HSP70, controls autophagy thus connecting and coordinating the two extreme ends of the homeostatic systems in the eukaryotic cell.